Comprehensive Study of Free Lunch Policy to Improve Human Development Index in the Perspective of Maqashid Syari'ah - Taufik Huda; Muhammad Afdhol Kusuma Ningrat; M. Fathur Rohim Arrozy; Johny Aninam; Misno (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is a qualitative research with descriptive approach that will detail one by one using descriptive narratives on each main topic used in this stud. The data used in this study are secondary data that researchers obtain from various sources that are certainly credible, quality, and commonly used in every study. The secondary data that researchers mention are in the form of scientific articles, books, magazines, and various other sources that are commonly used in every study.  The result in this article show that maqashid syari'ah or known as the purpose of the existence of sharia is everything that is produced for the benefit of the community. Thus it can be concluded that policies that are in line with the perspective of maqashid syari'ah are policies that can produce benefits for the community. The Free Nutritious Lunch Policy aims to increase the Human Development Index of children in Indonesia. It is true that according to a number of theories explained above, the Human Development Index is most influenced by the level of health and the level of human life expectancy. Based on this, it can be concluded that the free lunch policy is in line with the perspective of maqashid syari'ah and can increase the Human Development Index in Indonesia.